68Ga-DOTATATE PET/CT in Focal Fatty Sparing of the Liver. (October 2019) - Hod, Nir; Levin, Daniel; Anconina, Reut; Taragin, Benjamin H.; Dudnik, Julia; Lantsberg, Sophie
Abstract : Abstract: 68 Ga-DOTATATE imaging is commonly used for the detection of metastatic disease in neuroendocrine tumors. We present a case of a 69-year-old woman postsurgery for lung carcinoid tumor in which sequential follow-up 68 Ga-DOTATATE PET/CT studies identified focal hepatic uptake that was presumed to represent a liver metastasis. However, correlative imaging with MRI revealed a focal fatty sparing of the liver composed of benign hepatic parenchyma at that area accompanied with diffuse liver steatosis in the background of the "pseudolesion." This report demonstrates a potential "false-positive" hepatic finding that can strikingly mimic a metastasis in neuroendocrine tumor imaging.